Chief Executive Officers Entrepreneurial Orientation, Dynamic Capabilities, and Firm Performance: The Moderating Effect of the Manufacturing Industry - Liu, Yueyue; Xi, Meng; Jia, Yingya; Geng, Xiulin (Frontiers in Psychology, 2021)
This study explores the implications of CEO entrepreneurial orientation for firm performance through corporate dynamic capabilities. It explores the moderating effects of firm industry type on the above indirect effect. Based on 188 matched sample data collected from vice chief executive officers (CEOs) of Chinese firms, this study found that CEO entrepreneurial orientation was positively related to corporate dynamic capabilities and firm performance and that corporate dynamic capabilities mediated the positive relationship between CEO entrepreneurial orientation and firm performance. Firm industry type moderated the direct effect of CEO entrepreneurial orientation on corporate dynamic capability, and the indirect effect of CEO entrepreneurial orientation on firm performance through corporate dynamic capability. Both direct and indirect effects were stronger in manufacturing enterprises. The findings enrich the CEO entrepreneurial orientation literature by extending the existing knowledge on its underlying mechanism and its impact on firm performance, as well as its boundary conditions.